(untitled) (Research, Society and Development, 2021)
Infectious and Parasitic Diseases (IPDs) are a major global public health problem. The presence of many rivers, streams, lakes and lagoons is conducive to the proliferation of mosquitoes in Alagoas State. This study aims to analyse practices and knowledges about IPDs transmitted by mosquitoes (Aedes sp., Lutzomya sp., Anopheles sp. and C. quinquefasciatus) among students from a school-community in Maceió, Alagoas. A survey instrument of IPDs and their vector mosquitoes was applied for high school students from a state school. Later, lectures on the diseases were given, a workshop for fabrication of mosquito nets was offered and a documentary by Fiocruz was shown. Regarding to the students, 57.34 % were females and 42.66% were males, age range 14 to 22 years-old. The results indicate that 97.90% of the waste generated in their homes is transported to the landfill; 98.60% of the students knew the importance of eliminating standing water to fight mosquitoes; and 39.86% of the participants believed that a cleaned house avoids places where the mosquito lays its eggs. During this process, students were interested in learning about the consequences of diseases and ways of preventing mosquito proliferation. The data reveals that students know the importance of avoiding mosquitoes and also know what to do to prevent the proliferation of vector mosquitoes. Therefore, they can be multipliers in order to increase good health and environmental practices.